PROFIL KONEKSI MATEMATIS SISWA KELAS IX SMP NEGERI 14 PALU DALAM MENYELESAIKAN MASALAH PADA MATERI TEOREMA PYTHAGORAS DITINJAU DARI KEMAMPUAN MATEMATIKA - Padang, Sery Londong; Hasbi, Muh.; Lefrida, Rita; Hadjar, Ibnu (Aksioma, 2025)
This study aims to obtain a description of the mathematical connection profile of grade IX students of SMP Negeri 14 Palu in solving problems in the Pythagorean theorem material reviewed from mathematical ability based on mathematical connection indicators. This type of research is descriptive research with a qualitative approach. The subject of this study is a student of SMP Negeri 14 Palu consisting of one student with high mathematical ability, one student with moderate mathematical ability and one student with low mathematical ability. Data is collected through written tests and interviews. The results of this study show that students with high mathematical ability: (1) can relate between mathematical concepts, namely the concepts of Pythagorean theorem and algebra, (2) can relate mathematics to physics subjects, (3) can relate mathematics to daily life. Students with moderate mathematical ability: (1) can relate between mathematical concepts, namely the concepts of Pythagorean theorem and algebra, (2) can relate mathematics to physics subjects, (3) can relate mathematics in daily life. Students with low mathematical ability: (1) cannot relate between mathematical concepts, (2) cannot associate mathematics with other sciences, (3) cannot associate mathematics in daily life.